INFLUENCE OF PROFITABILITY, EPS ,ROE,PBV, NPM ON STOCK PRICES OF MANUFACTURING COMPANIES IN IDX - Jholant Bringg Luck Amelia Br.Sinaga; Stephanie; Iin Kenari (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This research aims to evaluate the impact on the stock prices of production firms, Earning per share, Equity return, Price Book Value, and Net Margin. Earnings per share, returns on equity, pricing book valuation, and net profit margin are the phenomena of growth in profitability and not a further increase in stock prices of manufacturers on the Indonesian stock bond. The methodology of sampling is intended for sampling. The samples collected were 198 analytical units. The results of the study demonstrate that profitability and net profit per share in industrial firms on the Indonesian Stock Börse for the period 2017 to 2019 do not have any part influence on Earning Per Share. Earning per share in the manufacturing firms of Indonesia affects the return on equity and the price of the book value in part. For the years 2017-2019, Indonesia Stock Exchange. Return on equity, price-book value and net profit margins concurrently impact stock price in the Indonesian Stock Exchange manufacturing businesses for the year 2017-19.